From Logos to Christos essays on Christology in honour of Joanne McWilliam - Leonard, Ellen M., 1933-; Merriman, Kate, 1948- (Waterloo, Ont. : Wilfrid Laurier University Press, 2010)
From Logos to Christos is a collection of essays in Christology written by friends and colleagues in memory of Joanne McWilliam. McWilliam was a pioneer woman in the academic study of theology, specializing in Patristic studies and internationally recognized for her work on Augustine. For countless students she was a teacher, a mentor, an inspiration. These fourteen essays are a fitting tribute to her memory. Written by recognized North American scholars, the essays explore various aspects of Christology, inviting the reader to probe the meaning and significance of Jesus Christ for today. T
Ancient applied Christology : appeals to Christ in Greek amulets in late antiquity / Theodore de Bruyn -- Jesus of Canada? Four Canadian constructions of the Christ figure / Mary Ann Beavis -- La christologie d'un apocryphe : une christologie apocryphe? Le cas des Actes de Thomas / Paul-Hubert Poirier et Yves Tissot -- Jesus in Augustine's anti-Manichaean writings / J. Kevin Coyle -- The seventh canon of Ephesus / J. Robert Wright -- Logos Christology today / Roger Haight -- Christ the transformer of culture : Augustine and Tillich / Peter Slater -- Hooker on divinization : our participation of Christ / David Neelands -- Logos ecclesiology revisited : the Church of the Triune God / Michael A. Fahey -- Deep Christology : ecological soundings / Elizabeth A. Johnson -- Neither male nor female : Christology beyond dimorphism / Pamela Dickey Young -- Theological implications of mobile hospitality / Deirdre Good -- Jesus died for our sins : redemption as an ethic of risk / Cynthia Crysdale -- Lord of two cities : christological or political realism in Augustine's City of God? / Jane Barter Moulaison.
Includes bibliographical references and index.
Includes some text in French.
Keywords: Jesus Christ -- Person and offices; Logos (Christian theology); Religion and ethics; Philosophy, Ancient; Philosophy; RELIGION / Christian Theology / Christology; Electronic books